A review of the sources and pharmacological research of morroniside - Shi, Pengliang; Zheng, Bingqing; Zhang, Shiyao; Guo, Qingmei (Frontiers in Pharmacology, 2024)
Morroniside (Mor) is the bioactive compound found in Corni Fructus (CF) [Cornaceae; Cornus officinalis Siebold & Zucc.], which has been used as medicine and food in China, Korea, and Japan for over 2000 years. This review summarises recent progress on Mor, specifically its distribution, isolation, detection, and various pharmacological effects. A literature survey of Mor was conducted using the electronic databases of Pubmed, ScienceDirect, CNKI, and Google Scholar. After removing TCM prescriptions-related standards, medicinal herb processing-related research, and other irrelevant literature， we obtained relevant information on Mor's biological and pharmacological properties. The main conclusions are as follows: Mor is widely distributed in the kingdom of plants, the method of extracting and isolating Mor is mature, and the technology of detecting Mor is accurate. Mor exhibits numerous pharmacological effects. Along with CF, Mor has renoprotective effects against diabetes, hepatoprotective effects from diabetes, triptolide, nonalcoholic steatohepatitis, and bone-protective effects against osteoporosis and osteoarthritis. Besides, researchers have also expanded other pharmacological effects of Mor, including neuroprotective effects against focal cerebral ischemia, spinal cord injury, and Alzheimer's disease; cardioprotective effects against acute myocardial infarction; protection of the digestive system from gastritis, inflammatory bowel disease, and colitis; protection of skin through promoting hair growth, wound healing, and surviving flaps; protection of lung from acute lung injury and pulmonary fibrosis; Moreover, Mor has the anti-obesity effect, antiinflammation effect in the eye, and improve follicular development. Overall, this review provides a comprehensive understanding of the pharmacological effects of Mor, from which the limitations of current research can be understood, which will help to facilitate future research.